Cardiovascular Risk Factor Profiles and Disease in Black Compared to Other Africans with Chronic Kidney Disease. (24th February 2021) - Hsu, Hon-Chun; Robinson, Chanel; Woodiwiss, Angela J.; Norton, Gavin R.; Dessein, Patrick H.
Abstract : Background and Objectives. The extent to which chronic kidney disease (CKD) impacts cardiovascular disease (CVD) in black Africans is uncertain. We compared cardiovascular risk factors and CVD between black and other African CKD patients. Methods . Cardiovascular risk factors, aortic and cardiac function, atherosclerosis extent, and cardiovascular event rates were assessed in 115 consecutive predialysis ( n = 67) and dialysis patients ( n = 48) including 46 black and 69 other (32 Asian, 28 white, and 9 mixed race) participants. Data were analysed in multivariable regression models. Results . Overall, black compared to other African CKD patients had less frequent carotid artery plaque (OR (95% CI) = 0.38 (0.16–0.91)) despite an increased cardiovascular risk factor burden. In receiver operator characteristic curve analysis, the Framingham score performed well in identifying non-black but not black CKD patients with carotid plaque (area under the curve (AUC) (95% CI) = 0.818 (0.714–0.921) and AUC (95% CI) = 0.556 (0.375–0.921), respectively). Black compared to other African predialysis patients experienced larger Framingham scores and more adverse nontraditional cardiovascular risk factors, impaired arterial and diastolic function but similar cardiovascular event rates (OR (95% CI) = 0.93 (0.22 to 3.87)). Among dialysis patients, black compared to other Africans had an overall similar traditional and nontraditional cardiovascular risk factor burden, similar arterial and diastolic function but increased systolic function (partial R = 0.356, p = 0.01 and partial R = 0.315, p = 0.03 for ejection fraction and stroke volume, respectively) and reduced cardiovascular event rates (OR (95% CI) = 0.22 (0.05 to 0.88)). Conclusion . Black compared to other African CKD patients have less frequent very high risk atherosclerosis and experience weaker cardiovascular risk factor-atherosclerotic CVD relationships. These disparities may be due to differences in epidemiological health transition stages. Among dialysis patients, black compared to other Africans have less cardiovascular events, which may represent a selection bias as previously documented in black Americans.